Agriculture and Rural Transformation in Burkina Faso: Does Land Rights Matter? - Mikémina PILO (African Journal on Land Policy and Geospatial Sciences, 2020)
In the search for rural transformation, this paper analyses the effect of agriculture on rural nonfarm entrepreneurship (NFE) highlighting the role of land rights and assesses the impact of rural NFE on households’ livelihood focusing on rural Burkina Faso. To achieve these objectives, the study uses two techniques: (i) propensity score matching technique to investigate the nonfarm entrepreneurship impact on farm households’ income; (ii) logistic regression to assess the role of agriculture in the development of nonfarm enterprises. Empirical estimates are based on the Living Standards Measurement Study-Integrated Surveys on Agriculture (LSMS-ISA) database of the World Bank. From the results we conclude that rural NFE is pivotal for rural transformation in Burkina Faso given that farm households that engage into NFE enjoy significantly higher per capita income and overall household income. The results allow us in addition to establish that on average, a farmer whose land rights are perfectly secured is more willing to engage into non-farm entrepreneurship activities.  Additional determinants of individual engagement into NFE are shocks, livestock size, age of household head, active female household members and land size. Farming experience has no effect on individual engagement into NFE. These findings call for a redefinition of the agricultural policy and programs of the country to explicitly include rural nonfarm entrepreneurship development strategies component. Such component could target pragmatic land lights policy and the enhancement of the capabilities of farm households to be entrepreneurial.